Analisis Pemilihan Kapal Selam Dalam Memperkuat Postur TNI AL Menggunakan Metode Fuzzy dan Analytical Hierarcy Process - I Made Budi Wirawan; Syarif Mustika Harinurdi; Achmnad Faisol (Rekayasa, 2022)
Submarines of very strategic value in their procurement are directed to realize a deterrence strategy and a balancing strategy with state actors that have the potential to threaten the sovereignty of the Indonesian state. In addition to threats, the procurement of submarines also considers the geographical constellation of Indonesia. The first step in procurement is to make an analysis in terms of selecting alternative submarines, both analysis of information and identification of various important and interrelated requirements regarding data from alternative submarines that will be selected. In this condition, it can be solved by using fuzzy AHP approach. The results obtained from the Fuzzy AHP method are the order of priority for selecting alternative submarines, namely Scorpene Class (0.398), Changbogo Class (0.220), Reis Class (0.191) and Gotland Class (0.191). Where the results of the importance of the main criteria are sequentially starting from the Strategic Requirement (Strareq) criteria of 0.409, Operation Requirement (Opsreq) of 0.318 and Technical Requirement (Techreq) of 0.273.